MRI AND CT IMAGE-BASED RADIOMICS DETECTION OF FUNCTIONAL LIVER RESERVE BEFORE SURGERY OR BIOPSY (World Bulletin of Public Health, 2024)
Despite significant advances in all areas of medicine, particularly dentistry, the treatment of patients with chronic ostitis remains an urgent problem for both dentists and scientists. The difficulties that arise in the treatment of periapical changes in chronic forms of ostitis are that tissue regeneration in the area of the root tip occurs 6-12-24 months after the end of endodontic treatment. Therefore, many scientists are developing new tools to stimulate and accelerate periapical regeneration processes and improving existing methods